A compact quad‐band band‐pass filter using novel stub‐loaded SIR structure. Issue 3 (March 2014) - Wei, Feng; Huang, Qiu Lin; Li, Wen‐Tao; Shi, Xiao‐Wei
Abstract A compact quad‐band band‐pass filter (BPF) based on a novel stub‐loaded step‐impedance resonator (SL‐SIR) is analyzed and designed in this article. The proposed SL‐SIR, which is found to have the advantages of introducing four narrow passbands and providing more degrees of freedom to adjust the resonant frequencies, is investigated by using even/odd mode analysis. A prototype of a quad‐band BPF centerd at 1.5, 2.5, 3.5, and 5.2 GHz is designed and fabricated. The simulated and measured results are in good agreement with each other. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:538–542, 2014